The Influence of Conflicts of Interest on Outcomes in the Lumbar Disc Arthroplasty Literature: A Systematic Review. Issue 16 (15th August 2019) - Guntin, Jordan A.; Patel, Dil V.; Cardinal, Kaitlyn L.; Haws, Brittany E.; Khechen, Benjamin; Yoo, Joon S.; Block, Andrew M.; Lalehzarian, Simon P.; Singh, Kern
Abstract : Study Design: A systematic review. Objective: The aim of this study was to determine the association between study outcomes and the presence of a conflict of interest (COI) in the lumbar disc arthroplasty (LDA) literature. Summary of Background Data: Previous studies have evaluated the efficacy of LDA as a surgical alternative to arthrodesis. As investigators may have financial relationships with LDA device companies, it is important to consider the role of COI on study outcomes. Methods: A systematic review was performed to identify articles reporting clinical outcomes of LDA. Any financial COIs disclosed were recorded and confirmed through Open Payments and ProPublica databases. Study outcomes were graded as favorable, unfavorable, or equivocal. Pearson Chi-squared analysis was used to determine an association between COI and study outcomes. Favorable outcomes were tested for an association with study characteristics using Poisson regression with robust error variance. Results: Fifty-seven articles were included, 30 had a financial COI, while 27 did not. Ninety percent of the conflicted studies disclosed their COI in the article. Studies with United States authors were more likely to be conflicted ( P  = 0.019). A majority of studies reported favorable outcomes for LDA (n = 39). Conflicted studies were more likely to report favorable outcomes than nonconflicted studies ( P  = 0.020). Articles with COIs related to consultant fees ( P  = 0.003), research funding ( P  = 0.002), and stock ownership ( P  < 0.001) were more likely to report favorable outcomes. Conclusion: This study highlights the importance for authors to accurately report conflicting relationships with industry. As such, orthopedic surgeons should critically evaluate study outcomes with regard to potential conflicts before recommending LDA as a surgical option to their patients. Level of Evidence: 3 Abstract : Supplemental Digital Content is available in the textAs investigators may have financial relationships with lumbar disc arthroplasty device companies, it is important to consider the role of conflicts of interest on study outcomes. This study demonstrates how conflicted studies are more likely to report favorable outcomes when compared with nonconflicted studies.